A New Paradigm for Higher Education Internationalization in Brazil? - Leal , Fernanda; Barreto Moraes, Mário César (International Higher Education, 2025)
This article discusses the new Brazilian government strategy aimed at the internationalization of higher education—the program Networks for Institutional Internationalization (CAPES-Global.Edu)—launched in July 2025. The objective is to analyze the directions of the internationalization of Brazilian higher education over the past 10 years, with some initial reflections on the characteristics of the new initiative and, specifically, its prospects for marking a new paradigm of internationalization for Brazil.